ANALISIS MAKRO EKONOMI,HARGA KOMODITAS,KINERJA PASAR MODAL AMERIKA DAN PENGARUHNYA TERHADAP PASAR MODAL INDONESIA ( PERIODE: MARET-JULI 2020 ) - Noviarti (Jurnal Manajemen, 2021)
This study aims to determine Macroeconomics, Community Prices, the performance of the American Capital Market and their influence on the Performance of the Indonesian Capital Market for the period March-July 2020. The sample method used is non-probability sampling method, and the sampling technique used is saturated sampling. This study uses time series data and is analyzed using the classical assumption test. In addition, multiple linear hypothesis test was also used, simultaneous F test, partial t test and determination coefficient test. From the results of the study it was found that simultaneously Macroeconomics was represented by the exchange rate, Community Prices were represented by world gold prices, the performance of the American Capital Market represented by the Dow Jones Index affected the Indonesian Capital Market represented by the IHSG in the March-July 2020 period. Partially, only the Dow Jones Index affects the Composite Stock Price Index, while the rupiah / dollar exchange rate and the world gold price have no effect on the Composite Stock Price Index (JCI) during the observation period from March to July 2020. It can be concluded that the decline in capital market performance in developed countries also affects the Indonesian capital market. The decline in the JCI was not due to the depreciation of the Rupiah, the increase in the price of gold but was caused by negative sentiment that continued to suppress economic performance globally as a result of investor panic due to the Covid 19 pandemic continuing to spread and there was no vaccine to overcome it.